The longitudinal effects of resisted sprint training using weighted sleds vs. weighted vests - Clark, K. P.; Stearne, D. J.; Walts, C. T.; Miller, A. D. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to determine the longitudinal effects of weighted sled (WS) and weighted vest (WV) sprint training on maximum velocity sprint performance and kinematics. Twenty male collegiate lacrosse players were randomly assigned to a WS group (n = 7) towing 10% body mass, a WV group (n = 6) loaded with 18.5% body mass, or an unresisted (UR) active control group (n = 7). All subjects completed 13 training sessions over 7 weeks. Pre- and post-test measures of sprint time and average velocity across the distance interval of 18.3 to 54.9 m were used to assess sprint performance, whereas high-speed video (300 Hz) and motion-analysis software were used to analyze stride length, stride rate, ground contact time, and flight time. A 3 × 2 repeated measures analysis of variance was performed for each dependent variable and revealed no significant between-group differences for any of the sprint performance or kinematic stride cycle measures. Effect size statistics suggested small improvements in 18.3- to 54.9-m sprint time and average velocity for the UR group but only trivial improvements for the WS and WV groups. With regard to sprint performance, the results indicate that WS and WV training had no beneficial effect compared with UR training. In fact, for the loads used by WS and WV in this study, UR training may actually be superior for improving sprint performance in the 18.3- to 54.9-m interval.